Weak Type Estimate of Singular Integral Operators on Variable Weak Herz-Type Hardy Spaces - Boulares, H. B.; Drihem, D.; Hebbache, W.
This paper is concerned with the boundedness prop-erties of singular integral operators on variable weak Herz spacesand variable weak Herz-type Hardy spaces. Allowing our pa-rameters to vary from point to point will raise extra difficulties,which, in general, are overcome by imposing regularity assump-tions on these exponents, either at the origin or at infinity. Ourresults cover the classical results on weak Herz-type Hardy spaceswith fixed exponents.
Keywords: Mathematics